The effect of banks' debt creation on price stability: evidence from Middle East and North Africa - Sayid Hassan Musse; Hassanuddeen Abdul Aziz;, Osman; Abdul Aziz, Hassanuddeen; Echchabi, Abdelghani (Inderscience Publishers, 2014)
The purpose of the study is to examine the possible influence of the current money creation process applied by the commercial banks through the fractional reserve system on the overall prices stability in the MENA countries. The study uses yearly data spanning from 2005 through 2011 for 15 MENA countries, and applies panel regression analysis based on the pooled data set. The results indicate that neither outstanding deposits nor outstanding loans do have a significant influence on inflation.